PERAN KEPUASAN PELANGGAN MEMEDIASI PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN LARISSA AESTHETIC CENTER DENPASAR - Mila, Mila; Santika, I Wayan (E-Jurnal Manajemen; Vol 10 No 9 (2021), 2021)
Self-care has become a necessity and a lifestyle for everyone, especially for women. The rapidly growing development of beauty clinics requires companies in the beauty sector to be able to understand every consumer behavior. The purpose of this study is to explain the effect of service quality, customer satisfaction, customer loyalty, to explain the role of customer satisfaction to mediate the effect of service quality on customer loyalty. This research was conducted at Larissa Aesthetic Center Denpasar. The sample in this study were people who already had a member or identification card at the Larissa Aesthetic Center in Denpasar City. The sampling method used was nonprobability sampling. The data collection method in this study is a survey method with interview techniques and using a questionnaire. Data were analyzed using descriptive statistical analysis techniques, path analysis, classical assumption test, sobel test and vaf test. The results showed that service quality has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer loyalty, customer satisfaction has a positive and significant effect on customer loyalty, customer satisfaction has a significant role in mediating the relationship between service quality and customer loyalty. The implications in this research are theoretical implications and practical implications. Keywords : service quality, customer satisfaction, customer loyalty.